Identificação de SNPs para uma anomalia de desenvolvimento em E. grandis e seus efeitos na estrutura proteica e interatoma - Martin, Leonardo Curi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Eucalyptus species have been successfully used for forest plantations. Some intrinsic features such as rapid growth, adaptability to various weather conditions and economic potential in energy production, fiber and solid wood, help to reduce pressure on tropical forests and associated biodiversity. Investments in research and development on molecular biology arebeing carried out by forestry sector in order to increase productivity gains. Since anomalous characteristics of progeny may generate productivity loss, gene identification linked to abnormalities are crucial for breeding programs. During a controlled crossing with Eucalyptus grandis, the Suzano Papel e Celulose enterprise detected an atypical Mendelian segregation 3: 1 (normal: abnormal). Significant phenotypic differences concerning height, stem base diameter, and leaf size appeared, as well as an unusual early death, when compared to normal plants. Previous studies identified a molecular tag attached to this anomaly. Sequence comparison analysis of eucalyptus database showed identity with Bet v1 PR10 protein family (Pathogenesis-related protein 10). However, gene involvement in developing such aberration is undetermined. Other studies found a transcriptional profile of contrasting phenotypes by RNAseq technique. Among differentially expressed genes by functional enrichment highlighted those belonging to Bet v1 families, chitinases class I, and thaumatin, all related to pathogenic response. This fact suggests that aberration is caused by the plant immune system activation (autoimmune response). To investigate the pathogenesis of such genetic disorder, three approaches were adopted: (i) SNPs identification among the differentially expressed genes of Bet v1 families, chitinase, and thaumatin, (ii) miRNAs identification with potential binding to mRNAs differentially expressed genes, and (iii) check of possible influence of differentially expressed gene products on ...

Espécies de Eucalyptus têm sido utilizadas com sucesso para plantios florestais devido ao seu rápido crescimento, sua capacidade de adaptação às diversas condições climáticas e pelo seu potencial econômico na produção de energia, fibra e madeira sólida, reduzindo assim a pressão sobre as florestas tropicais e a biodiversidade associada. Investimentos em pesquisas e desenvolvimento estão sendo realizados pelo setor florestal, no intuito de aumentar os ganhos de produtividade através da pesquisa na área da biologia molecular. Visto que características anômalas nas progênies podem gerar perdas na produtividade, a identificação e caracterização dos genes relacionados a anomalias são muito importantes no auxílio em programas de melhoramento genético. Ao realizar um cruzamento controlado de Eucalyptus grandis, a empresa Suzano Papel e Celulose detectou uma anomalia com segregação mendeliana 3:1 (normais:anômalas) na progênie. As características eram bem significativas se comparadas com as plantas normais, tais como diferenças na altura, diâmetro da base do caule, tamanho das folhas e morte em poucos meses. Estudos anteriores identificaram uma marca molecular ligada à anomalia, e análises de comparação da sequência contra o banco de dados de eucalipto demonstrou identidade com proteínas da família Bet v1 PR10 (Pathogenesis-related protein 10), embora não estivesse claro o envolvimento deste gene no desenvolvimento da anomalia. Outros estudos traçaram o perfil transcricional dos fenótipos contrastantes pela técnica de RNAseq. Dentre os genes diferencialmente expressos, através do enriquecimento funcional, destacaram-se os pertencentes as famílias Bet v1, quitinase classe I e taumatina, todos relacionados à resposta contra patógenos, sugerindo que a anomalia seja causada pela ativação do sistema imune da planta (resposta autoimune). Com o intuito de se obter mais informações sobre à patogênese da...
SNPs discovery for a developmental anomaly in Eucalyptus grandis and effects on protein structure and interactome
Keywords: Genetica vegetal; Eucalipto - Melhoramento genético; Eucalyptus grandis; Acido ribonucleico; Polimorfismo (Genetica); Polimorfismo de nucleotídeo único; Polymorphism, Single Nucleotide